CLINICAL SPECTRUM AND DIAGNOSTIC OF NEUROFIBROMATOUS IN YOUNG AGES: SERIAL CASE - Rahmaditta, Allyssa; Rahmawati, Dessika (MNJ (Malang Neurology Journal), 2026)
Background: Neurofibromatosis and schwannomatosis are neurocutaneous syndromes characterized by a genetic predisposition to the formation of Schwann cell tumors. Phenotypic overlap between NF2 (Neurofibromatosis Type 2)-related schwannomatosis and non-NF2 schwannomatosis often presents diagnostic challenges. Objective: To report two cases of neurofibromatosis in young patients with distinct clinical manifestations, highlighting diagnostic and therapeutic aspects. Contents: A case series study involving two patients diagnosed with neurofibromatosis at Dr. Saiful Anwar General Hospital, Malang, in 2025. Data were collected from anamnesis, physical examination, and ancillary tests including radiologic and histopathologic evaluations, followed by analysis to establish diagnosis and treatment planning. The first case, a 30-year-old male, presented with progressive limb weakness and bilateral hearing loss. MRI revealed bilateral vestibular schwannomas and multiple intradural schwannomas, consistent with NF2-related schwannomatosis. The second case, a 30-year-old female, experienced multiple neuropathic pain sites and tender subcutaneous nodules. Biopsy confirmed neurofibroma, consistent with non-NF2 schwannomatosis. Management included decompressive surgery and symptomatic therapy. Conclusion: Clinical manifestations of NF2 and schwannomatosis often overlap; thus, an integrated approach combining clinical, radiologic, histopathologic, and genetic findings is essential for accurate diagnosis. A multidisciplinary approach is required to optimize prognosis.